Community-based quit smoking intervention using 5A’s and 3A’s approaches in Sarawak, Malaysia - Muhammad Siddiq Daud; Md Mizanur Rahman; Sabrina binti Lukas; Kamarudin Bin Kana; Merikan Bin Aren; Rudy Ngau Ajeng; Mohd Faiz Gahamat (International Journal of Public Health Science (IJPHS), 2022)
Rising worldwide adolescent smoking necessitates national and global research to establish intervention methods. This research evaluated the efficacies of 5A’s and 3A’s interventions. Self-reported quit-smoking attempts were the outcome measure. Methods: Six villages were randomly selected and equally divided into three groups: 5A’s, 3A’s, and Control (no intervention). Five hundred nineteen current participant-smokers aged 13-17 were followed-up by phone (first and third months) and face-to-face interviews (sixth and ninth months). Most 3A’s participants (n = 12, 7.1%) quitted smoking in the first month, followed by the 5A’s (n = 9, 5.3%) and the Control (n = 3, 1.9%).  In the third month, 5A’s participants topped the rank (n = 16, 10.7%), followed by the 3A’s (n = 14, 9.2%), and Control (n = 5, 3.4%). As per sixth-month follow-up, the 5A’s group maintained its position on top of the list (n = 27, 21.4%), followed by the 3A’s (n = 22, 17.1%) and the Control (n = 5, 4.0%). The majority of 5A’s participants quitted smoking after nine months (n=36, 33.0%), followed by the 3A’s (n = 27, 25.5%), while Control maintained its position (n = 5, 5.0%). 5A intervention prevented adolescent smokers from becoming chronic smokers.